Studying the development of fluvial landforms in the Berettyó-Körös Region using geoinformatic methods - Tóth , Csaba Albert; Barkóczi , Norbert; Mcintosh , Richard William; Plásztán, Zsolt József (Acta Geographica Debrecina Landscape & Environment series, 2016)
Development of fluvial landforms from 1980 till nowadays was studied based on digital elevation maps (DEM) composed from contour lines of topographic maps, field data obtained by RTK GPS and aerial photos taken by a drone. Greatest denudation of 6-9 metres was measured in the eastern side of the erosional valley at Pocsaj caused by piping and mass movements. As a result, the valley widened and slightly deepened. Since 1980 around 1-2 metres of accumulation and erosion of similar rate have been measured in the secured floodplain environment dissected by abandoned beds, point-bars and swales at Kismarja. These values, however, rather reflect the geometric uncertainties and deficiencies of the contours of topographic maps than real land changes. Therefore topographic maps can give reliable basis for studying the development of lowland landforms only if they depict adequately large sized (minimum 100 x 100 m) positive or negative forms with great height difference as well (minimum 8-10 m). Accuracy of DEMs composed from aerial photos using photogrammetric methods – taking off height faults caused by vegetation – is around the same as that of the models created on the basis of RTK GPS measurements.